La pastoral urbana en la Iglesia Latinoamericana: Memoria histórica, relectura teológica y proyección pastoral (Teología, 2020)
The text offers a historical memory, a theological reading and a pastoral projection of the recent path of the Church in the evangelization of Latin American urban culture. It focuses on the contributions of the post-conciliar Bishops General Conferences of Latin America and the Caribbean, and other initiatives and publications of the Latin American Episcopal Council (CELAM). It updates the ecclesial memory that wants to meet the challenge of increasing urbanization (Medellín) proposing the evangelization of the modern city (Puebla), the inculturation of the Gospel in our cities (Santo Domingo) and a new urban pastoral that wants to be radically missionary (Aparecida). The author proposes the assumption of the anthropological challenges of an inculturated and intercultural urban ethos; promoting faith in a God that dwells among men in the cities; imagining personal and comunitary mediations in order to communicate the life in Christ in urban culture; going to the suburbs to share the Gospel with the poor and remote. The Spirit and the Church can reinvent the new Babel in a new Pentecost.
Keywords: City; Urban Culture; Church in Latin America; New Evangelization; Inculturation; Urban Pastoral; General Conference of Aparecida